PENGGUNAAN PLATFORM LEARNSOCIAL DALAM MENINGKATKAN KEMAMPUAN LISTENING MAHASISWA PRODI PENDIDIKAN BAHASA INGGRIS STKIP KUSUMANEGARA - Megawati Megawati; Neng Nurwiatin; Ivon Mukaddamah (Sekolah Tinggi Pariwisata Mataram, 2021)
This research used quantitative research. It was use Classroom Action Research (PTK). In COVID 19 era, research used Platform Learnsocial to improve students’ listening skill. The aims of the research is to knowing that Platform learn social can improve students’ listening skill, to knowing that Platform learn social can be used as one of the media in learning Listening. This research consists of two cycle. Every cycle consists of four steps. The first steps is planning, second is acting, third is observing and the fourth is reflecting. Result of the research in Cycle I, there is 50% students pass in listening skill and 50% students fail in listening skill. Then in Cycle II, there is 83% students pass in listening skill and 16% students fail in listening skill. It can be shown that Platform Learnsocial can be one of the media that suitable to improve students’listening skill.